Corncob-based biorefinery: A comprehensive review of pretreatment methodologies, and biorefinery platforms. (April 2022) - Gandam, Pradeep Kumar; Chinta, Madhavi Latha; Pabbathi, Ninian Prem Prashanth; Velidandi, Aditya; Sharma, Minaxi; Kuhad, Ramesh Chander; Tabatabaei, Meisam; Aghbashlo, Mortaza; Baadhe, Rama Raju; Gupta, Vijai Kumar
Abstract: The xylan richness and comparatively lower extractives and ash, make the corncob lignocellulose an excellent source for many biorefinery products and objectives. The unique packing of lignocellulose material in corncob makes it susceptible to different pretreatment approaches that are less effective on other types of biomass feedstocks. More specifically, after pretreating corncob, up to 99% delignification, 100% hemicellulose solubilization, and around 95% cellulose recovery can be achieved. Accordingly, corncob-derived chemical platforms have found many applications ranging from conventional use to newer products like supercapacitors. Platform sugars and ethanol have been the major products derived from corncob's cellulose and hemicellulose, whereas the production of xylooligosaccharides is the second most reported objective. Corncob lignin is mostly valorized for its phenols. Traditional and emerging pretreatment approaches, were reported, and in some reports, corncob-lignocellulose is valorized without a pretreatment. The data reported over the past fifty years on the corncob pretreatment in the SCOPUS database was compiled and analyzed throughout this review. The efficiency of different pretreatment methodologies and their effect on downstream yields were compared in detail. Graphical abstract: Image 1 Highlights: Pretreatment is the vital bottleneck in the path to valorising lignocellulose biomass. Around 50 different biorefinery platforms/ objectives were reported using corncob as the source. 41% of reported works involved separation of platform sugars from corncobs and subsequent alcohol fermentation. Only 14% of the reported works involved exclusive hemicellulose valorisation. Application of lifecycle analysis approach to compare different pretreatment methods is still a major research gap.